Improved process and results of civic education (Pkn) with cooperative model course review horay in elementary school - Reinita (Fakultas Ilmu Pendidikan UNP)
The problem of this study is low process and result of students learning in Civic Education (PKn). The purpose of this study is to improve the process and the result of students learning in Civic Education (PKn). The type of research used is classroom action research with qualitative and quantitative approach. The subjects of this study were teachers and 27 students in grade 4th. This research shows that there was an increase of lesson plan from cycle I that is average 76,78% to 92,85% in cycle II. Implementation of learning on teacher aspect and student aspect increased from average 77,25% in cycle I to be 93.18% in cycle II. And the increase of students learning outcomes increased from the average of 74.45 increased to average of 90.16 in cycle II. It can be concluded that by using classroom action research with qualitative and quantitative approach (Course Review Horay Model) can improve process and result of students learning.